A method of dynamic union control for intelligent mould bed system in ship block building. (3rd August 2022) - Wang, Zhen; Jing, Xuwen; Cai, Youhui; Liu, Jinfeng; Zhu, Tianhu; Zhou, Honggen; Tang, Mingming; Li, Lei; Li, Chunjin; Dong, Lei
ABSTRACT : Mould bed is the most important equipment to control the deformation in the process of block construction. However, its height needs to be controlled separately based on the known height, and it affects the construction precision of block severely. Therefore, a dynamic union control method is proposed in this paper. Firstly, in order to realize the union control of mould bed system, the distribution types of mould bed system are defined, and a dynamic relationship is established, the determination algorithm number, position and height compensation layer number is proposed. Secondly, the fuzzy PID control based on neural network is used to realize the adaptive control of height according to the changes of pressure, so as to control the construction quality better of block. Thirdly, the MATLAB/Simulink module is used to verify the proposed method and shows that the response time is significantly shortened by 41% and 37.5% respectively.